2000
DOI: 10.1128/jb.182.17.4862-4867.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Gene Encoding Sulfopyruvate Decarboxylase, an Enzyme Involved in Biosynthesis of Coenzyme M

Abstract: The products of two adjacent genes in the chromosome of Methanococcus jannaschii are similar to the amino and carboxyl halves of phosphonopyruvate decarboxylase, the enzyme that catalyzes the second step of fosfomycin biosynthesis in Streptomyces wedmorensis. These two M. jannaschii genes were recombinantly expressed in Escherichia coli, and their gene products were tested for the ability to catalyze the decarboxylation of a series of ␣-ketoacids. Both subunits are required to form an ␣ 6 ␤ 6 dodecamer that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 35 publications
1
59
0
Order By: Relevance
“…However, since detection of this activity, it has been possible to show that spermidine biosynthesis in Gram-positive bacteria and in archaea is similar to the related pathway in Gram-negative bacteria and in eukarya (Sekowska et al 2000). Finally, MJCyc provides strong evidence for the presence of the pathway for biosynthesis of Coenzyme M, an important cofactor in methanogenesis: the first two reactions have been identified in M. jannaschii and attributed to this pathway (MJ0255, 2r-phospho-3-sulfolactate synthase and MJ1140, 2-phosphosulfolactate phosphatase) (Graupner et al 2000, Graham et al 2001a). …”
Section: Discussionmentioning
confidence: 93%
“…However, since detection of this activity, it has been possible to show that spermidine biosynthesis in Gram-positive bacteria and in archaea is similar to the related pathway in Gram-negative bacteria and in eukarya (Sekowska et al 2000). Finally, MJCyc provides strong evidence for the presence of the pathway for biosynthesis of Coenzyme M, an important cofactor in methanogenesis: the first two reactions have been identified in M. jannaschii and attributed to this pathway (MJ0255, 2r-phospho-3-sulfolactate synthase and MJ1140, 2-phosphosulfolactate phosphatase) (Graupner et al 2000, Graham et al 2001a). …”
Section: Discussionmentioning
confidence: 93%
“…In addition to TPP, PO, ALS and GXC each require FAD (Bertagnolli and Hager 1993;Cromartie and Walsh 1976;Chang et al 1993;Koland JG 1982). Finally, SPDC and PPDC both consist only of PP-and Pyr-domains (Graupner et al 2000). In SPDC, the PPand Pyr-domains form the separate subunits (α-and β-) of an α 2 β 2 -heterotetramer.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfopyruvate decarboxylase of the coenzyme M pathway, found in methaneforming bacteria (38), was identified as the closest homolog. Studies of the sulfopyruvate decarboxylase from Methanococcus jannaschii (39) have shown that the native enzyme is a dodecamer of 6 ␣-subunits (ComD 169 amino acids long; 34% sequence identity with the N-terminal half of the Ppyr decarboxylase) and 6 ␤-subunits (ComE 169 amino acids long; 39% sequence identity with the C-terminal half of Ppyr decarboxylase). It may be inferred that the ␣-and ␤-subunits of the sulfopyruvate decarboxylase correspond to N-terminal and Cterminal domains of the Ppyr decarboxylase.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfopyruvate decarboxylase (39) and Ppyr decarboxylase are more distant members of a family of TPP-and Mg(II)-dependent decarboxylases that includes acetohydroxy acid synthase/acetolactate synthase (40), benzoylformate decar- boxylase (41), glyoxylate carboligase, indole pyruvate decarboxylase, pyruvate decarboxylase, the acetyl phosphate-producing pyruvate oxidase, and the acetate-producing pyruvate oxidase (42) (sequence identities between B. fragilis Ppyr decarboxylase and these proteins with a sequence range of 23-29%). The chemical reactions catalyzed by these enzymes are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%